European Union funded project on the development of a whole complement deficiency screening ELISA—A story of success and an exceptional manager: Mohamed R. Daha. Issue 1 (November 2015) - Würzner, Reinhard; Tedesco, Francesco; Garred, Peter; Mollnes, Tom Eirik; Truedsson, Lennart; Turner, Malcolm W.; Sommarin, Yngve; Wieslander, Jörgen; Sim, Robert B.
Highlights: An ELISA to screen for complement deficiencies was developed during an EU grant. Moh Daha guided this European consortium involving 12 scientists and a SME, Wieslab. The final result was a scientific publication and a commercially successful kit. In a follow-up grant the group is looking into further applications of this assay. Successful research & friendship guided by an exceptional manager: Moh Daha. Abstract: A whole complement ELISA-based assay kit, primarily designed to screen for deficiencies in components of the complement system was developed during a European Union grant involving more than a dozen European scientists and a small-medium enterprise company (Wieslab, which later merged into Eurodiagnostica). The consortium was led by Prof. Mohamed R. Daha who had already guided a preceding European grant which prepared the ground for this endeavor to create a novel and sophisticated complement measurement tool. The final result of the grant was a scientific publication (Seelen et al., 2005, J. Immunol. Methods 296, 187–198) and a commercially available complement deficiency screening kit, WIESLAB ® Complement system Screen. Thereafter, the group decided to carry on with a grant, located at Innsbruck Medical University, and supported by royalties and unrestricted educational grants from Eurodiagnostica, Malmö, entitled "Search for Applications for WIESLAB ® Complement system Screen (SAW)" with the aim to look for further applications of this assay. During the latter project the group organized several scientific meetings aimed at evaluating the use of the assay as well as developing further branches of its platform. A look back over almost two decades reveals a great story of excellent research which was also commercially successful, fulfilling the aims of European Union grants. It is also a story of ageless friendship, only possible due to the vision and guidance of an exceptional manager: Moh Daha.